PENGARUH PENAMBAHAN AQUADEST DAN AIR ACCU (H2SO4 30%) TERHADAP ARUS DAN TEGANGAN DARI SEL ACCU DENGAN MENGGUNAKAN AIR SINGKONG KARET (MANIHOT GLAZIOVII. M.A) - Yuni Satria Ningsih (Department of Physics – Universitas Negeri Padang UNP, 2014)
The waste produced by the tapioca flour that made from Manihot glaziovii.M.A it is divide into two types, namely, solid waste and liquid waste. Solid waste can be used as organic fertilizer, but for liquid waste is not optimally utilized. Liquid waste is contain cyanide compounds by 8,27 mg/L that can generate electric current and potentially as an electrolyte solution. After that the writer analyze this research on liquid waste from Manihot glaziovii M.A water. The purpose of this research is to know the current and voltage value of the manihot glaziovii M.A with water that uses the cell battery. From this research the writer find the results obtained the value of current (I) and voltage (V) for each variation of the solution as follows: test solution to ASK for 1A; 3V, to ASK solution: Aq (70: 30 = 1A; 2 .6V), (65: 35 = 1A; 2, 4V), (60: 40 = 1A; 2, 2V) and ASK for a solution: Ac (70: 30 = 1A; 4, 4V), (65: 35 = 1A; 4, 7V), (60: 40 = 1A, 28V; 4). Water accu has (I) and (V) of 1A; .6V. Next on the measurement value of degree on acidity (pH) of the test solutionASK: Aq has a pH of 5, to ASK > pure pH = 4,69, while to ASK: Ac pH 3.5 <. I and V highest produced by ASK: air conditioning. So the results of this research is indicate that Manihot glaziovii.M.A has the potential as a solution of accu is more environmentally friendly and not harmful. Keywords: Manihot glaziovii M.A, Cell Accumulator, Current (I), Voltage (V), and pH